2008
DOI: 10.1111/j.1525-142x.2008.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Competent stripes for diverse positions of limbs/fins in gnathostome embryos

Abstract: Every vertebrate species has its own unique morphology adapted to a particular lifestyle and habitat. Limbs and fins are strikingly diversified in size, shape, and position along the body axis. This diversity in morphology suggests the existence of a variety of embryonic developmental programs. However, comparisons of various embryos suggest common mechanisms underlying limb/fin formation. Here, we report the existence of continuous stripes of competency for appendage formation along the dorsal midline and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 44 publications
4
59
0
Order By: Relevance
“…Current evolutionary models of the origin of vertebrate appendages suggest that ancestral fin folds acquired Shh expression in posterior mesenchyme, which enabled Development 139 (9) development of the fin bud (Dahn et al, 2007;Tanaka et al, 2002;Yonei-Tamura et al, 2008). Given that the Hand2-Shh morphoregulatory network controls both teleost pectoral fin and tetrapod limb bud development (Galli et al, 2010;Gibert et al, 2006), and as both genes are expressed in fin buds of cartilaginous fish (Dahn et al, 2007;Tanaka et al, 2002;Yonei-Tamura et al, 2008), the direct interaction of HAND2 with Shh cis-regulatory regions would define an evolutionarily conserved module for initiation of appendage development (Charite et al, 2000;Galli et al, 2010;Yelon et al, 2000). The apparent differences in the genetic systems (Xu and Wellik, 2011) (this study) that control fore-and hindlimb bud induction indicate that these two types of paired appendages might have arisen by differential control of the Hand2-Shh module.…”
Section: Lim-homeodomain Proteins During Limb Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evolutionary models of the origin of vertebrate appendages suggest that ancestral fin folds acquired Shh expression in posterior mesenchyme, which enabled Development 139 (9) development of the fin bud (Dahn et al, 2007;Tanaka et al, 2002;Yonei-Tamura et al, 2008). Given that the Hand2-Shh morphoregulatory network controls both teleost pectoral fin and tetrapod limb bud development (Galli et al, 2010;Gibert et al, 2006), and as both genes are expressed in fin buds of cartilaginous fish (Dahn et al, 2007;Tanaka et al, 2002;Yonei-Tamura et al, 2008), the direct interaction of HAND2 with Shh cis-regulatory regions would define an evolutionarily conserved module for initiation of appendage development (Charite et al, 2000;Galli et al, 2010;Yelon et al, 2000). The apparent differences in the genetic systems (Xu and Wellik, 2011) (this study) that control fore-and hindlimb bud induction indicate that these two types of paired appendages might have arisen by differential control of the Hand2-Shh module.…”
Section: Lim-homeodomain Proteins During Limb Developmentmentioning
confidence: 99%
“…The molecular and genetic systems for correct patterning and growth of the limb bud have been studied extensively, mainly in mouse and chick model systems, and have demonstrated that the forelimb and hindlimb buds share most of their developmental programs (Zeller et al, 2009). Studies of various animal models, such as chondrichthyes (cartilaginous fishes) and teleost fish, have illustrated that limb/fin developmental systems are evolutionarily conserved, and suggested lateral fin folds as the origin of paired appendages (Tanaka et al, 2002;Yonei-Tamura et al, 2008). Throughout the development of the limb and fin in animals examined so far, SHH is a central factor (Dahn et al, 2007;Krauss et al, 1993;Riddle et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The endoskeletal elements proximal to fin rays in the teleost pectoral fin are poorly patterned along the proximodistal (PD) axis, whereas limb endoskeletal elements exhibit a well-organized sequential pattern (stylopod, zeugopod and autopod) . Many studies suggest that fin structures transformed into limbs by changes in genetic and developmental programs during tetrapod evolution (Sordino et al, 1995;Metscher et al, 2005;Ahn and Ho, 2008;Yonei-Tamura et al, 2008;Sakamoto et al, 2009;Woltering and Duboule, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It takes 16-24 hr for FGF7 to induce the AER in the ectoderm (Yonei-Tamura et al, 1999); this may be too late to induce the limb mesenchyme in the flank through the ectopic AER, because the flank LPM has started dying by stage 17/18, as shown in Figure 6. To test this hypothesis and to examine the function of PSM on suppressing limb bud formation in the flank, we ablated the PSM at the flank level and implanted an FGF7-soaked bead; we used FGF7, because it is reported to be more effective for AER induction than FGF10 (Yonei-Tamura et al, 2008) (Fig. 8E).…”
Section: Effect Of Fgf Signaling On Apoptosis In the Flank Lpmmentioning
confidence: 99%
“…One soaked bead was then inserted between the LPM and the overlying ectoderm. We used FGF7 rather than FGF10, because it is known to exhibit a similar activity, with a generally stronger effect (Yonei-Tamura et al, 2008).…”
Section: Implantation Of Beadsmentioning
confidence: 99%